PENGARUH KEBIASAAN TIDUR TERHADAP FOKUS BELAJAR SISWA: TIDUR AWAL VS. BEGADANG - Wahyu Purwanto; Najibah Balasad; Ries Ardianto; Puji Lestari (LPMP Provinsi DKI Jakarta, 2025)
Early sleeping habits play an important role in improving the quality of students' learning concentration. This study aims to compare the impact of early sleeping habits and staying up late habits on the learning concentration of grade IX students at SMP Al Ikhlash Lumajang in the 2024/2025 academic year. The study used a descriptive quantitative approach with data collection techniques through interviews and observations of 32 students who were divided based on their sleep patterns. The results showed that students who went to bed early (before 22.00) had an average learning concentration level of 85%, while students who often stayed up late (after 24.00) only reached 60%. These findings indicate that sleep duration and quality have a significant effect on students' cognitive abilities, especially concentration during learning. The implications of this study support the importance of healthy sleep habits as a strategy to improve the quality of education